Factors contributing to neonatal birth asphyxia in public health facilities of Mopani District, Limpopo Province - Makhumisane, Mphonyane (My University, 2024)
Introduction and background: Birth asphyxia is a severe medical problem worldwide, especially in developing countries, and the main contributor to neonatal mortality and morbidity. Birth asphyxia is an oxygen deficit at delivery, which can lead to severe hypoxic organ damage (heart, lungs, liver, gut, and kidneys), but brain damage is of most concern and perhaps the least likely to heal quickly or entirely. Purpose: This research aimed to determine contributory factors leading to neonatal birth asphyxia among professional midwives working in public health facilities of Mopani district, Limpopo Province. Research method: The researcher used a quantitative, descriptive, cross-sectional research design. The population of this research study was all professional nurses with midwifery qualifications working in public health facilities of Mopani district, Limpopo Province. Participants (n=139) were sampled using simple random sampling techniques. Self-developed questionnaires were used as an instrument for data collection. The data was analysed using Statistical Package for Social Sciences (SPSS) version 27. Validity and reliability were ensured, and ethical considerations were adhered to in this research study. Results: The most contributing factor of neonatal birth asphyxia was Prolonged labour n=138(100%) followed by meconium-stained liquor n=114(82.6%) and Delayed emergency caesarean n=108(78.3%). Conclusion: Prolonged labour/ delayed maternal 2nd stage of labour was identified as one of the leading health-related factors contributing to neonatal birth asphyxia. Meconiumstained liquor was the most contributing factor to neonatal birth asphyxia caused by maternal-related factors. Education and training programmes are recommended for professional midwives which will increase their knowledge and skills on proper management of women in labour including the antenatal period to reduce birth complications that might lead to birth asphyxia.
Thesis (M. (Nursing)) -- University of Limpopo, 2024
Keywords: Birth asphyxia; Factors; Neonatal; Preterm; Mortality; Midwives; Neonatal intensive care -- South Africa --Limpopo; Neonatology -- South Africa -- Limpopo; Asphyxia neonatorum -- South Africa -- Limpopo; Hypoxic-ischemic encephalopathy